The relationship between the functional movement screen, star excursion balance test and the Beighton score in dancers. Issue 1 (2nd January 2020) - Armstrong, Ross
ABSTRACT: Objectives : To determine the association between the Functional Movement Screen (FMS), Star Excursion Balance Test (SEBT) and the Beighton Score (BS) in dancers with implications for performance and injury. Methods : The study was of cross-sectional design and included 47 female university dancers (age: 20.4 ± 0.7 years, height: 160.5 ± 5.8 cm; mass: 55.6 ± 4.8 kg). Participants completed the FMS and the anterior, posteromedial and posterolateral reach components of the SEBT and hypermobility was assessed via the BS. Results : A fair significant correlation existed between FMS composite and total BS (r = 0.37, p = 0.01). For individual elements of the screening tools, there were 24 significant correlations between the FMS and the BS, 11 significant correlations between the FMS and SEBT and 4 significant correlations between the SEBT and BS. Conclusion : The FMS and the BS correlations highlighted the importance of the deep squat in functional movement and the relationship between FMS mobility elements and the BS. The significant correlation between the FMS and the BS may suggest that they capture similar information. The active straight leg raise and shoulder mobility measurements should be considered key elements to measure during screening.